Therapeutic Effects of Zoledronic Acid-Loaded Hyaluronic Acid/Polyethylene Glycol/Nano-Hydroxyapatite Nanoparticles on Osteosarcoma - Xu, Yan; Qi, Jingqi; Sun, Wei; Zhong, Wu; Wu, Hongwei (Frontiers in Bioengineering and Biotechnology, 2022)
Zoledronic acid (ZOL) has been approved as the only bisphosphonates for the prevention and treatment of metastatic bone diseases with acceptable safety and tolerability. However, systemic or direct injection of ZOL often causes severe side effects, which limits its clinical application. Here, an innovative nano-drug delivery system, ZOL loaded hyaluronic acid/ polyethylene glycol/ nano-hydroxyapatite nanoparticles (HA-PEG-nHA-ZOL NPs), has been found to effectively inhibit the proliferation of three types of human osteosarcoma cell lines (143b, HOS, MG63) at 1-10 μmol/L, while with low cell cytotoxicity on normal cells. The NPs significantly enhanced the apoptosis related protein expression and tumor cell apoptosis rate. The NPs could also inhibit the proliferation of osteosarcoma cells via blocking the S phase of cell cycle. In the orthotopic osteosarcoma nude mice model, local injection of the HA-PEG-nHA-ZOL NPs stimulated tumor necrosis, apoptosis and granulocyte infiltration in the blood vessels. Altogether, the ZOL nano-delivery system possesses great potential on local treatment to prevent local tumor recurrence and can be applied in clinical osteosarcoma therapy.